Role of Healthcare Professionals in Influencing Consumer/Patient Behaviour towards Medication Compliance - Balachandran, Rahul (2008)
Patient compliance to medications or non-adherence to schedule is a widely debated topic across the world owing to its far reaching consequences as medication non-adherence among new age group is moving rapidly upwards even when the whole world is witnessing continuous expansion in the field of education, healthcare deliverance and other economic and scientific advancements. The objective of this study was to evaluate the role played by healthcare professionals in changing this distressing pattern of prescription non-adherence by measuring their influence on the behaviour of patients. Throughout this study the patient is considered as a consumer, but not always an end user of the product, unless otherwise stated and both terms are interchanged to suit the context. In order to satisfactorily conduct the research, quantitative survey techniques are employed with 5 point (Likert, 1932) type scales using Ã¢ÂÂAgreeÃ¢ÂÂ, Ã¢ÂÂDisagreeÃ¢ÂÂ, Ã¢ÂÂStrongly DisagreeÃ¢ÂÂ, Ã¢ÂÂStrongly AgreeÃ¢ÂÂ and Ã¢ÂÂNeutralÃ¢ÂÂ type survey questions, numbering 20. Out of these 20 questions, 5 were questions on socio-demographics to get an idea about the quality and diversity of the responses. A pool of 107 respondents, majority males from 3 multi-speciality hospitals in the South Indian state of Kerala was selected and questionnaire responses were obtained and analysed using specialised statistical program SPSSTM. The use of quantitative survey was found to be appropriate and is justified since the nature and type of the study involved mostly patients and also taking due thought that a qualitative semi-structured interview within a hospital setup involving ailing patients with poor health condition is undesirable. The questionnaire was put across by taking relevant literature into consideration and majority of the findings were consistent with the previous literature. The findings indicate that healthcare professionals have a significant impact on patients when it comes to medication compliance and this was put to test by analysing the roles played by cost and health motivation in the behaviour of the consumer.